Neurological Immune-Related Adverse Events in Patients Treated with Anti-PD-1 agent, Pembrolizumab: A Case Series - Khosravi, Sepehr; Khoeini, Tara; Rahattalab, Fateme; Haghi Ashtiani, Bahram (Case reports in neurology, 2025)
Background This case series highlights the various clinical manifestations of pembrolizumab-induced neurological adverse events, offering insights into the spectrum of immune-related neurological adverse events associated with immune checkpoint inhibitor (ICI) therapy. Case Presentation We present five patients who received pembrolizumab as a part of their treatment. They exhibited a variety of clinical manifestations, which included central nervous system involvement and necrotizing myopathy, each responding differently to therapeutic interventions. Among the participants, there were two cases of myopathy, one case of demyelinating polyneuropathy, one individual whose myasthenia gravis had worsened, and one patient diagnosed with encephalitis. The patients experienced symptoms with varying degrees of severity, leading to different responses in their clinical treatment, and one patient ultimately passed away due to complications. Conclusion Neurological immune-related adverse effects (n-irAEs) are rare, and their identification poses a challenge due to their complexity and the presence of underlying autoimmune and paraneoplastic disorders. The expected prognosis for n-irAEs is unclear, presenting a range of complete recovery rates and differing mortality outcomes. The increased frequency of ICI usage increases the probability of an immune response, necessitating healthcare professionals to identify new symptoms in immunotherapy patients. Side effects differ from conventional chemotherapy and necessitate different therapeutic approaches.